KEARIFAN LOKAL KAOMBO HAMOTA (KAOMBO) DI DESA BURANGASI KECAMATAN LAPANDEWA KABUPATEN BUTON SELATAN - Risnawati Risnawati; Wa Ode Sifatu; La Janu (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2019)
This study aims to reveal the community's compliance with the local wisdom of Kaombo Hamota in the Burangasi community in South Buton Regency. The underlying theory is Geertz's thought of "From the Native 's Point of View" with ethnographic methods. The results of the study show that there is still public compliance with the hamota group because of the impact felt directly by both groups and outside groups, and all types of ages. The impact is in the form of signs both visible and invisible to the eye. However, there are also a handful of groups of juvenile delinquents who take several actions to avoid the effects of the Kaombo Hamota such as urinating on the roots of the tree, throwing animal droppings into the tree they wish to steal, and making a bonfire below. As a result of these actions, they feel pain like swollen swelling, itching, growing a number of boils that festering reddish color on both legs and both hands. Such a condition are enriched by the community due to stealing in the garden that has a hamota kaombo and is a byword in the community. Local people also believed that the illness could be treated by asking for help from the Bhisa who installed the hamota kaombo.